Allergy to Insulin Analogs in Gestational Diabetes - Kholoud A. Ghamri, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Since human recombinant insulin preparations has been introduced in medicine, allergies to insulin have rarely been reported, especially in pregnant women, who experience immune system alterations that are due to physiologic changes that occur during pregnancy. We describe a 41-year old woman who developed gestational diabetes during the second trimester and was initially treated with insulin aspart and detemir. She complained of itching, redness and a burning sensation at insulin injection sites a few weeks after administration of both insulin types. This warranted cessation of her current insulin regimen and switching to Humulin R and Humulin N due to the unavailability of insulin lispro in the hospital. In addition, patient couldn’t afford buying it from outside the hospital. Her serum glucose was well controlled on this insulin regimen, and no allergic reaction was reported by the patient. Insulin allergy is an unusual finding in pregnancy, which can be managed by switching treatment regimens.